2023
DOI: 10.1017/jfm.2023.584
|View full text |Cite
|
Sign up to set email alerts
|

Exact coherent structures in fully developed two-dimensional turbulence

Dmitriy Zhigunov,
Roman O. Grigoriev

Abstract: This paper reports several new classes of unstable recurrent solutions of the two-dimensional Euler equation on a square domain with periodic boundary conditions. These solutions are in many ways analogous to recurrent solutions of the Navier–Stokes equation which are often referred to as exact coherent structures. In particular, we find that recurrent solutions of the Euler equation are dynamically relevant: they faithfully reproduce large-scale flows in simulations of turbulence at very high Reynolds numbers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Even if complete statistical coverage is challenging, the ability to search for exact recurrent flows with particular physical properties is exceptionally useful if the goal is to understand the importance of individual dynamical events within well-known statistical phenomena like the energy cascade. It is also worth noting that the three-dimensional case may differ substantially from the two-dimensional flows studied here: in 2D we expect that some of the solutions we obtain at higher may connect to solutions of the Euler equations as ( 41 , 43 ), which are expected to take the form of domain-filling vortices, while wall-bounded turbulence is expected to require a more complex multiscale description with eddies of varying sizes attached to the boundaries ( 44 ). Early studies of weak, transient turbulence in 3D minimal flow units have shown that the statistics of individual UPOs can sometimes closely resemble the turbulence ( 8 ) itself which provides cautious optimism for the 3D case.…”
Section: Discussionmentioning
confidence: 80%
“…Even if complete statistical coverage is challenging, the ability to search for exact recurrent flows with particular physical properties is exceptionally useful if the goal is to understand the importance of individual dynamical events within well-known statistical phenomena like the energy cascade. It is also worth noting that the three-dimensional case may differ substantially from the two-dimensional flows studied here: in 2D we expect that some of the solutions we obtain at higher may connect to solutions of the Euler equations as ( 41 , 43 ), which are expected to take the form of domain-filling vortices, while wall-bounded turbulence is expected to require a more complex multiscale description with eddies of varying sizes attached to the boundaries ( 44 ). Early studies of weak, transient turbulence in 3D minimal flow units have shown that the statistics of individual UPOs can sometimes closely resemble the turbulence ( 8 ) itself which provides cautious optimism for the 3D case.…”
Section: Discussionmentioning
confidence: 80%
“…In the absence of forcing, dissipation, bottom topography and beta effect, the final state of such a turbulent flow is a pair of contra-rotating vortices. The search for the spatial structure of final vortex states in 2-D turbulence has motivated the original work on minimum-enstrophy vortices (hereafter MEVs) (Leith 1984 a , b ), and more recently, a search for exact coherent structures in 2-D turbulent flows (Zhigunov & Grigoriev 2023). In his seminal paper, Leith used variational principles to derive the velocity profile of an axisymmetric vortex in 2-D incompressible flows, with minimal enstrophy for a given energy, angular momentum or circulation.…”
Section: Introductionmentioning
confidence: 99%